Caloric Vestibular Stimulation Induced Enhancement of Behavior and Neurotrophic Factors in Chronic Mild Stress Induced Rats - George, Sherly Deborah; Archana, Rajagopalan; Parasuraman, Subramani (Frontiers in Pharmacology, 2022)
Background: Caloric Vestibular Stimulation (CVS) is a non-invasive technique for stimulating the vestibular system. The vestibular system maintains equilibrium and acts as a moderator of mood, emotional control, and stress levels. Stress is a disruption of psychological, behavioral, and physiological homeostasis that affects people of all ages in today's world. Thus, modest therapeutic procedures like vestibular stimulation can be practiced to effectively reduce stress. Hence, the purpose of the study was to determine the effect of vestibular stimulation on improving behavioral alterations and neurotrophic factors in rats exposed to Chronic Mild Stress (CMS). Methodology: The study employed twenty-four healthy male Sprague Dawley rats divided into four groups (n=6). CMS was induced for 28 days with a variety of stimuli. Bilateral CVS with hot water (temperature ≈ 400C) was started on Day 14 of CMS and continued for 15 days. On days 1, 15, and 28, locomotor activity (LA), wire grip strength (WGS), fall off time (FT), and immobilization time (IT) were measured, and the data were analyzed statistically. Additionally, neurotrophic factors such as Brain Derived Neurotrophic Factor (BDNF) and Glial cell line-Derived Neurotrophic Factor (GDNF) were observed in rats' hippocampus. Results: On days 15 and 28, the CMS-induced group showed a significant reduction in LA, WGS, FT and IT in comparison to the control group. On day 28, the CVS-induced group demonstrated a significant increase in WGS, FT and IT when compared to the CMS group. Immunohistochemical analysis revealed that animals subjected to CMS had decreased BDNF and GDNF expression compared to the control group, indicating neuronal dysfunction in the hippocampus in response to stress. However, therapy with CVS increased BDNF and GDNF expression, thereby regenerating damaged hippocampus nerve terminals. Conclusion: The findings of the current study revealed that CVS is a safe and simple neuroprotective treatment against stress and a promising non-invasive technique for overcoming the motor symptoms associated with it. The findings may pave the way for future research and therapeutic applications of CVS for stress management.